The Economics of the Antitrust Process - Coate, M.B.; Kleit, A.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 1996)
This book focuses on the antitrust process and how that process affects the efficiency of antitrust law enforcement. The contributors share a wide range of experiences in the antitrust process, including academia, the legal environment, and both private and public sectors. The book deals first with merger activities, followed by non-merger enforcement initiatives and concludes with an examination of the future role of antitrust.
1 Introduction: The Economics of the Antitrust Process -- 2 Overenforcement in the Hart-Scott-Rodino Second Request Process -- 3 The Merger Guidelines As Applied -- 4 Simulation as an Alternative to Structural Merger Policy in Differentiated Products Industries -- 5 The Efficiencies Defense in Merger Cases -- 6 Buyers, Market Power, and Market Definition -- 7 Merger Enforcement at the Reagan/Bush FTC -- 8 Winners and Losers in the Settlement of Merger Litigation -- 9 Efficiency Lost?: The Microsoft Consent Decree -- 10 Predatory Pricing in the Retail Trade: The Wal-Mart Case -- 11 Guilt by Association: An Analysis of Nonprice Horizontal Restraint Enforcement -- 12 Antitrust, Economics, and (3z(BReality(3y(B.s
Keywords: Industrial organization; Microeconomics; Industrial Organization; Microeconomics